Numbers of Follicles, Pregnancy, Expression of Reactive Oxygen Species (ROS), and Ovarian Genes in Sheep Treated with Vitamin E, L-Carnitine, and Fish Oil - Hatami, M.; Yarahmadi, H. M.; Fakhraei, J.; Ahmadi, A. (Tropical Animal Science Journal, 2022)
This study was performed to evaluate the effects of vitamin E, L-carnitine, and fish oil on the numbers of follicles, pregnancy, Reactive Oxygen Species (ROS) expression, and expression of several ovarian genes in sheep. For this purpose, 256 sheep were randomly divided into eight experimental groups. They were given a diet supplemented with vitamin E, L-carnitine, and fish oil alone and in combination. FBS, estradiol levels, size of the follicles, and pregnancy rate were observed. Expressions of Superoxide Dismutase 1 (SOD1), Superoxide Dismutase 2 (SOD2), Transforming Growth Factor –β (TGF-β), and Peroxisome Proliferator-Activated Gamma Receptor (PPAR-γ) genes were measured using Reverse Transcription-Polymerase Chain Reaction (RT-PCR), and ROS was measured using fluorescence microscope. At the time of mating and pregnancy, the highest number of follicles and pregnant ewes were observed in the groups supplemented with fish oil and antioxidants (p